Perubahan warna lempeng resin akrilik yang direndam dalam larutan desinfektan sodium hipoklorit dan klorhexidin (The color changes of acrylic resins denture base material which are immersed in Sodium hypochlorite and chlorhexidine) - David David; Elly Munadziroh (Dental Journal (Majalah Kedokteran Gigi), 2005)
One of the acrylic resins properties is the water absorption including color fluids and chemically fluids that affect on the color changes of the acrylic resins. This laboratory experiments studied sodium hypochlorite and chlorhexidine effect on the color changes of acrylic denture base resins material. The study was conducted by immersing heat cured acrylic plate samples of 26 mm of diameter and 0.4 mm of thickness in sodium hypochlorite for 10; 70 and 140 minutes and chlorhexidine for 15; 105 and 210 minutes. Seven samples were used for each experiment. An optical spectrometer BPX-47 type photo cell and a digital microvoltage were used for the color changes observation. The statistical test used were t-test, One-way ANOVA and LSD with 0.05 significance degree level. The results of the studied showed that the color of acrylic resins denture base plate changed after immersion in sodium hypochlorite for 70 and 140 minutes and chlorhexidine for 105 and 210 minute of immersion.